(untitled) (Revista Latino-Americana de Enfermagem, 2010)
This descriptive exploratory study analyzed user satisfaction with the care received at a Family Health Unit in Ribeirão Preto, Brazil. In total, 40 users from families registered in the FHU were selected, using key informants and the snowball sampling technique, and interviewed. Thematic content analysis was used to analyze the empirical material. Interviewees were mostly female, over 50 years, resident in the catchment area of the unit for 10-30 years, had incomplete primary education and also did not perform work outside the home. The analysis identified three themes: access, team-user interaction and organization of work in the FHU. The subjects of this study expressed satisfaction with the accessibility provided together with the caring attention given to them, marked by a team-user interaction that takes place in a friendly and patience manner. Although not totally satisfied, the majority of users would recommend the health service to someone due to its quality.